In-depth examination of human nature in Chinese philosophy using psychological research - Teo, Darrelle Jia Xin (Nanyang Technological University, 2022)
We will be using psychology to further understand Xunzi’s stance that human nature is bad in comparison to Mencius’s stance that human nature is good. Our first focus will be on exploring human’s innate inclination which led us to conclude that one’s moral compass is innately neutral. Next, through learning, we explore how human nature can change from neutrality to goodness. Lastly, we will examine how moral learning can affect one’s behaviour.